From Menu to Memory: Enhancing Repurchase Intentions Through Menu Variety and Customer Experience (International Journal of Scientific Research and Management (IJSRM), 2025)
The purpose of this research is to analyze the impact of menu variety and customer experience on repurchase intention, mediated by customer satisfaction in the café industry. The sample consists of 278 respondents who are customers of 10 retail café brands in Jakarta. The study uses snowball sampling as its sampling method. The data analysis combines quantitative and descriptive techniques. The Structural Equation Model (SEM) is utilized for quantitative analysis with LISREL software. The results show that menu variety and consumer experience have a direct impact on customer satisfaction. Additionally, customer satisfaction serves as a mediator between menu variety and consumer experience in relation to repurchase intention. This study provides valuable insights for café business practitioners to enhance menu variety and improve customer experience in order to increase satisfaction and encourage repurchase intention.